2010
DOI: 10.1039/c0jm02061c
|View full text |Cite
|
Sign up to set email alerts
|

Thermoreversible ionogels with tunable properties via aqueous gelation of an amphiphilic quaternary ammonium oligoether-based ionic liquid

Abstract: The gelation of the amphiphilic quaternary ammonium oligoether-based ionic liquid (AMMOENG100) with water is addressed. This approach allows the preparation of thermoreversible ionogels with high ionic conductivity (up to 60 mS cm(-1)), remarkable mechanical properties (storage moduli above 10(5) Pa a value comparable to the mechanical properties of some rubbers), and melting points in the range from -20 to 53 degrees C. These properties can be easily tuned in a broad range by varying the water (and/or inorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 32 publications
1
42
0
Order By: Relevance
“…28,29 Schubert et al found the thermoreversible gelation of an amphiphilic quaternary ammonium-type ionic liquid/water mixture, which exhibited high conductivity probably due to the controllable water content and the additional inorganic salts. [30][31][32] We also reported the gelation of ionic liquids using novel low-molecular-weight gelators and revealed that the gelation did not affect the ionic conductivities of ionic liquids. 23,24 Yanagida et al demonstrated the feasibility of ionogels to the solid-state dye-sensitized solar cells using a lowmolecular-weight gelator.…”
mentioning
confidence: 92%
“…28,29 Schubert et al found the thermoreversible gelation of an amphiphilic quaternary ammonium-type ionic liquid/water mixture, which exhibited high conductivity probably due to the controllable water content and the additional inorganic salts. [30][31][32] We also reported the gelation of ionic liquids using novel low-molecular-weight gelators and revealed that the gelation did not affect the ionic conductivities of ionic liquids. 23,24 Yanagida et al demonstrated the feasibility of ionogels to the solid-state dye-sensitized solar cells using a lowmolecular-weight gelator.…”
mentioning
confidence: 92%
“…This shortcoming is overcome by gelling ILs 22,23 using different approaches such as: (1) solidification of ILs by polymers [24][25][26][27][28][29][30] ; (2) addition of inorganic nanoparticles, 31,32 carbon nanotubes, [33][34][35] and low-molar mass compounds, 36,37 and (3) Aqueous gelation of ILs. 38,39 Specifically, ion-gels consisting of a swollen polymeric network in an IL constitute a promising class of solid state electrolytes owing to their combined advantages of good mechanical properties and high ionic conductivity which have potential applications in Li-ion batteries, electrochemical devices, sensors, electromechanical actuators, gas separation membranes, and dye-sensitized solar cells. 31,32,[40][41][42][43][44][45][46] Most of the studies on iongels derived from polymers are based on doping of ILs with polymers and in situ polymerization (or crosslinking) of vinyl monomers in ILs.…”
Section: Introductionmentioning
confidence: 99%
“…[7] The design and synthesis of low molar mass gelators are also effective methods. [8] However, these methods and techniques for the preparation of IL-based gels present several limitations, ranging from expensive materials to complex synthetic procedures, [9] which make them less attractive Recently, we have demonstrated a facile one-step synthetic strategy for the preparation of IL-based cross-linked polymeric nanogels (CLPNs) by the conventional radical copolymerization of a phosphonium-based IL (PIL) and the cross-linkers ethylene glycol dimethacrylate (EGDMA) and divinylbenzene (DVB) in selective solvents. [10] Nevertheless, when the imidazolium-based IL (ImIL), 1-vinyl-3-(ethoxycarbonyl)methyl imidazolium chloride was copolymerized with a cross-linker under the same conditions, the copolymers precipitated from the solvent, resulting in particles in the submicrometer range.…”
mentioning
confidence: 99%